Microcalcareous seaweeds as sentinels of trophic changes and CO2 trapping in transitional water systems. (November 2020) - Sfriso, Adriano; Buosi, Alessandro; Adelheid Wolf, Marion; Sciuto, Katia; Molinaroli, Emanuela; Moro, Isabella; Mistri, Michele; Munari, Cristina; Augusto Sfriso, Andrea
Graphical abstract: Highlights: The presence of microcalcareous macroalgae was studied in the Italian lagoons. Macroalgal growth was mainly affected by changes in the pH of the water column. Small algae are a Litmus Test Paper Strip for environmental quality assessment. Carbonated are accumulated in surface sediments by small calcareous macroalgae. The CO2 abatement occurred in environments of good-high ecological conditions. Abstract: Microcalcareous epiphytic seaweeds (MES) are macroalgae more sensitive than aquatic angiosperms to environmental degradation and, with their presence/absence, these species act like sentinels providing useful information on the ecological status of environments. In this study, we analyzed the environmental parameters in water column and surface sediments in relation to macrophyte variables from 257 sites, distributed in the main Italian transitional water systems (TWS). The results showed that MES are strongly correlated to pH changes, the main parameter that regulates their presence/absence. The optimal growth range is between pH 7.80 and 8.35; out of these values their growth is reduced or hampered. In oxidized sediments the carbonate crusts, composed by Mg-Calcite (an unstable compound that in the sediments quickly turns into calcite), can permanently trap up to 2.47 tonnes ha −1  yr −1 of CO2, increasing sediment thickness of approx. 0.06–0.21 mm yr −1 .